A minimum number of motile spermatozoa are required for successful fertilisation through artificial intrauterine insemination with husband's spermatozoa. (22nd May 2013) - Cao, S.; Zhao, C.; Zhang, J.; Wu, X.; Zhou, L.; Guo, X.; Shen, R.; Ling, X.
Summary Intrauterine insemination (IUI) is an effective, noninvasive, relatively simple and cheap method of infertility treatment. Many factors that affect IUI outcomes have been studied. However, there is no consensus about the optimal number of motile spermatozoa inseminated (NMSI) required for a reasonable chance of pregnancy after IUI. In this retrospective study, we aimed to assess the relationship between NMSI and the pregnancy rate after IUI with husband's spermatozoa. Couples who had either primary or secondary infertility for more than one year were recruited from the Department of Reproduction, Nanjing Maternity and Child Health Hospital, China, between January 2007 and December 2010. Overall, 1153 IUI cycles with husband's spermatozoa were performed in 645 women after ovarian stimulation. Factors that have previously been associated with a successful fertilisation after IUI were assessed. A total pregnancy rate of 13.88% was obtained. The pregnancy rate was only 4.05% if less than 2 × 106 motile spermatozoa were used, but this rose to 14.55% when more than 2 × 106 motile spermatozoa were inseminated. We therefore conclude that IUI can be performed when the NMSI exceeds 2 × 106. With this recommendation, IUI with husband's spermatozoa can be used to treat many more infertile couples.